Neuro-Ophthalmology Practice During Covid-19 Pandemic - Yuri Dwi Mayasari; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2022)
Introduction: Ophthalmology practice including neuro-ophthalmology (NO) adopted the American Academy of Ophthalmology recommendation to provide only urgent or emergent care during the COVID-19 pandemic. Objective: This report aimed to present demographical and patient visit data regarding the characteristic of outpatient in neuro-ophthalmology clinic and to evaluate the patients regulation and priority mitigation according to IOA guideline during COVID-19 pandemic. Methods: Retrospective study using medical record data of neuro-ophthalmology outpatients at Dr. Cipto Mangunkusumo Hospital from April-June in 2019 and 2020. Result: There were 207 visits from 160 patients during the pandemic, which was 33.9% of the total visits before pandemic. Most patients were reffered from internal referral (54.5%).  However, new patients from external referral mostly came with onset of more than 2 weeks (40.6%). Most common diagnosis during pandemic were NAION (12.6%), toxic optic neuropathy (8.7%), and paretic eye movement disorder (7.7%). The diagnosis were classified further into neuro-ophthalmology clinic guideline and IOA guideline based on diagnosis and tele-ophthalmology. The most common category were non-priority patients (55.6%), 3B priority level (26.5%), and first priority level (59,9%), respectively. Conclusion: A major difference characteristic of neuro-ophthalmology outpatients during pandemic was the number of patients visit. New patients mostly came from internal and local (Jabodetabek) referral which can be caused by mobility limitation, new hospital regulation and patients insecurity due to COVID-19. Priority mitigation in this study found non-priority patients were the majority who visited the clinic during COVID-19 pandemic, which may need further evaluation on referral and triage systems.